Delay Analysis Of Unloading Activities On The Ship MV. Kartini Baruna - Yeti Komalasari (IWJ : Inland Waterways Journal, 2022)
Tanjung Jati, Jepara PLTU Port is a steam power plant port that distributes electrical energy on the islands of Java and Bali. In its activities, the Tanjung Jati,Jepara PLTU Port unloads coal to produce electrical energy. In carrying out the unloading of cargo in MV. Kartini Baruna often occurs delays that are detrimental to shipping companies and power plants. From the results obtained from this study is the occurrence of delays in loading and unloading activities due to unloading equipment, unsuitable loading procedures, and due to weather. This is due to the lack of care and maintenance on loading and unloading equipment and errors in loading and unloading procedures on ships.In order to increase the productivity of the work for the PLTU Tanjung Jati Port in improving the smoothness of loading and unloading activities, it is recommended to provide training and skills for operators in order to facilitate coal loading and unloading activities and increase competence regarding the mechanism of unloading equipment.